Sugars and non-transmissible diseases - CHIRLICI, Alexei; RUBANOVICI, Vladislav; CEBANU, Serghei; RIMIS, Constantin; CURTEANU, Ala (One Health & Risk Management, 2022)
Introduction. Sugar consumed in reasonable quantities plays a beneficial role for the human body. In recent decades, however, it has been found that increased sugar consumption has negative effects on the health of the population. Material and methods. The paper presents a synthesis of official international and national documents and bibliographic sources on the occurrence of certain non-communicable diseases (NCDs) as a result of excessive sugar consumption. A focused search of literature sources was conducted using the Google Scholar search engine, PubMed, Research for Life, and Medline databases. The criteria for selecting the items included health problems caused by excessive sugar consumption. Results. Excessive sugar consumption contributes to the emergence of various NBTs such as circulatory system diseases, type 2 diabetes and a. Excessive sugar consumption has a major contribution to the phenomenon of overweight and obesity with its consequences. Excess sugar in the daily diet is one of the main causes of tooth decay. According to WHO recommendations, complex, multi-sectoral interventions are needed to reduce sugar consumption. Conclusions. In order to prevent NCDs associated with the nutritional factor, especially with excessive sugar consumption, in the Republic of Moldova, it is important to implement cost-effective interventions both socially and economically.